Control of Cultivable IAA-Producing Bacteria by the Plant Arabidopsis thaliana and the Earthworm Aporrectodea caliginosa - Ruben Puga-Freitas; Samir Abbad; Agnès Gigon; Evelyne Garnier-Zarli; Manuel Blouin (Applied and Environmental Soil Science)
Some soil microorganisms are involved in the complex interactions with plants and earthworms, through the production of indole acetic acid (IAA) which modifies plant growth and development. In a factorial experiment testing the impact of the presence/absence of plants and earthworms on IAA production by cultivable bacteria, we observed that plants were decreasing IAA production of 43%, whereas earthworms were increasing it of 46%. In the presence of both plant and earthworms, IAA production was as low as in the presence of plant control, showing that plants influence on IAA production by microorganisms prevails on earthworm influence. We discuss functional reasons which could explain this result.